Persepsi Mahasiswa Tentang InterprofessionalEducation (Ipe) Di Universitas Muhammadiyah Surakarta - Israbiyah, Siti Rohmah, Enita Dewi,S.Kep.,Ns.,MN (2016)
In this era of the global, a health workers in the hook to give the quality of health services. A quality service can be derive from a good collaboration between a profession as doctor, nurse and pharmacist in cooperation team. One effort in realizing effective collaboration between professions need to the practice of collaboration since the early through the learning process by the way the train students education used a strategic interprofessional Education (IPE). This study aims to determine the perceptions students on interprofessional education (IPE) at Universitas Muhammadiyah Surakarta. This study with the design of analysis descriptive quantitatif and use the cross sectional approach. Based on data from students who have attended the IPE in May 2016 at UMS obtained 70 respondents in the Faculty of Medicine and Faculty of Pharmacy. The result of measurement perception show that students has a good perception about IPE 87.1% and only 11.4% have the perception of being. The conclusion of this study showed that the students of general medicine and pharmacy have a good perception of the IPE related to the importance of cooperation between the profession. This proves that the presence of IPE learning process will make students more effective cooperation between professions. Therefore, the expected health education institutions such as doctor, pharmacy, nursing, nutrition, physiotherapy, etc to perform and more consistenly apply IPE that research can be performed on all student health education at Universitas Muhammadiyah Surakarta. As well, student health education can work in collaboration with a single profession but it can contribute from each profession that integrates did care services to patients. Keywords : IPE, Perception, Undergraduate student, Health, Medical, Pharmaceutical, Nursing.